Stereotaxic Thalamotomy for the Relief of Intractable Pain: CEM-thalamotomy - Tsubokawa, Takashi; Urabe, Miyoshi (The Tohoku Journal of Experimental Medicine, 1965)
Lesions were made in the nucleus centrum medianum by a stereotaxic technique in 15 cases suffering from intractable pain. The lesson was made unilaterally in 8 and bilaterally in 7. All of the cases were relieved of intract-able pain immediately after the operation without any loss of other sensa-tion. However, unilateral thalamotomy showed a transient effect, while bilateral thalamotomy showed a persistent sufficient effect, for relief of diffuse, poorly localized pain. There was no operative death or severe complication in this series. After the operation of bilateral CEM-thalamotomy, no change in the EEG was seen. No alteration of consciousness was observed except in 2 eases whose lesion extended to the nucleus parafascicularis or pretectal region. This operative procedure, CEM-thalamotomy, was an appropriate operation for intractable pain caused by malignant tumor.